Kurikulum Muatan Lokal Aksara Arab Melayu dalam Meningkatkan Literasi Melalui Kearifan Lokal di Kota Jambi - Iryani, Eva; Yusup, Agung; Jufri, Salman; Hasibuan, Tuti Hardianti; Nurazzelena, Nurazzelena (Arabi : Journal of Arabic Studies, 2024)
This study aims to explain the Local Content Curriculum of Arabic-Malay Script in Improving Literacy Through Local Wisdom at the Nurul Iman Seberang Islamic School in Jambi City. The research method used by the researcher is a descriptive qualitative approach, data obtained through observation, interviews and documentation conducted at the Nurul Iman Seberang Madrasah in Jambi City. The results of the study indicate that the implementation of the Local Content Curriculum of Arabic-Malay Script in the Arabic-Malay subject taught from grade VII to grade IX, the learning resources or reference books used are in the form of books provided by the school. The challenges in implementing the implementation of this local content curriculum are students who come from general educational backgrounds and are not yet familiar with the hijaiyah letters. The efforts made are in learning, teachers carry out special learning with a coaching system for students who find it difficult to learn Arabic-Malay Script.